The Methods of Choice for Extracellular Vesicles (EVs) Characterization - Szatanek, Rafał (Int J Mol Sci, 2017)
In recent years, extracellular vesicles (EVs) have become a subject of intense study. These membrane-enclosed spherical structures are secreted by almost every cell type and are engaged in the transport of cellular content (cargo) from parental to target cells. The impact of EVs transfer has been observed in many vital cellular processes including cell-to-cell communication and immune response modulation; thus, a fast and precise characterization of EVs may be relevant for both scientific and diagnostic purposes. In this review, the most popular analytical techniques used in EVs studies are presented with the emphasis on exosomes and microvesicles characterization.